2017
DOI: 10.4314/ijbcs.v11i3.5
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of raw and processed unripe <i>Carica papaya</i> fruit pulp and its contribution to dietary diversity and food security in some peasant communities in Nigeria

Abstract: Processed unripe Carica papaya fruit pulp is used as soup ingredient in some Nigerian communities but the nutritional value of the variously processed forms is largely unknown. The thrust of this study was to determine the nutritional quality of traditionally processed unripe C. papaya fruit pulp using AOAC methods. The proximate evaluation of the raw, dried-uncooked and dried-cooked samples revealed variation in nutrient contents (g/100 g): moisture (7.84±0.15-26.07±0.04), carbohydrate (55.82±0.18-63.00±0.58)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
2
5
2
1
Order By: Relevance
“…This further confirms that the peels of Carica papaya (ripe and unripe) as presented in this study are sufficient to meet the magnesium need of cattle. The results are in contrast with the observations of Martial-Didier et al ( 2017) who reported 19.11 mg/100g for the ripe peels of Carica papaya and 22.33 mg/100g reported for the unripe fruits of Carica papaya by Okon et al (2017).…”
Section: Proximate and Mineral Composition Of Ripe Carica Papaya Frui...contrasting
confidence: 94%
“…This further confirms that the peels of Carica papaya (ripe and unripe) as presented in this study are sufficient to meet the magnesium need of cattle. The results are in contrast with the observations of Martial-Didier et al ( 2017) who reported 19.11 mg/100g for the ripe peels of Carica papaya and 22.33 mg/100g reported for the unripe fruits of Carica papaya by Okon et al (2017).…”
Section: Proximate and Mineral Composition Of Ripe Carica Papaya Frui...contrasting
confidence: 94%
“…As shown in Table 2, Amaranthus cruentus contained the largest amount of magnesium (210.1±.29 mg/100g) among the studied In Amaranthus Cruentus, authors found magnesium as 248 mg/100g [18,24], Valcárcel-Yamani and Lannes [16] found ranged at 279.2 -319.0 mg/100g which was higher than the present study. Okon et al [25] found 22.33± 0.88 mg/100g in raw Carica papaya, Ali et al [26] as ranged between 10 to 33 mg/100g which was contrasting with present research. In this study, Solanum lycopersicum contains the lowest amount of magnesium 9±.45 mg/100g.…”
Section: Content Of Magnesium (Mg)contrasting
confidence: 85%
“…Dietary fats also increase the palatability of food by absorbing and retaining flavours (Antia et al, 2006;Ilodibia et al, 2014). The relatively low fat in C. oliterius shows that the leaves can be recommended as weight reducing diet and can therefore be consumed in large quantities with safety without risk of cardiovascular disease, obesity and other related diseases (Okon et al, 2017;Loucou et al, 2018). The ash content of a plant part is a reflection of its mineral elements.…”
Section: Discussionmentioning
confidence: 99%